The Influence of Individual, Social Environmental and the Effectiveness of Rehabilitation Program on Relapse of Drug Addiction - Ibrahim, Fauziah (2008)
A report by National Drug Agency has revealed that a total of existing 32,808 addicts, 15,389 new addicts and another 17,419 relapsed addicts were registered with official agencies nationwide in 2005. In a country of just over 27 million, the figure is appalling. It means that almost 3,000 addicts are registered every month. This alarming figure, especially among relapsed addicts has brought into questions on factors contributing to the problem. This study was conducted to examine the influence of three main factors, which are individual, social environmental and rehabilitation program effectiveness on the incidence of drug addict on relapse. Self- administered questionnaires were used to gather data. The sample consisted of 400 drug addict on relapse cases which were selected through the method stratified random sampling and systematic random sampling from eight Rehabilitation Centers throughout Peninsular Malaysia. Research Instruments were developed and adopted from various sources. The quantitative data were analyzed using various statistical data analysis methods; descriptive tests, Pearson correlation and multiple regression analysis (stepwise). The findings indicated that 93.6% of relapsed addicts surveyed have a medium and high degree potential of becoming relapse again. The analysis shows that relapsed addicts have the characteristics of having negative emotion, suffering social pressure and interpersonal conflict which puts them in a suffer high risk situation to relapse once freed from the rehabilitation program. The study also revealed that the great majority of the respondents surveyed had low self-confidence. The support from their respective employers and society was found not encouraging. The study discovered that individual factors (self-confidence r=-.790, p<.05) and social environmental factor (family support, r=-.207, p<.05, employer support r=-.193, p<.05 and society support (r=-.315, p<.05) bore significant relationship with drug addict on relapse. The study also identified three predictive variables: self-confidence (Beta=.743), support from society (Beta=.155) and family support (Beta=.086) with the total of 65.3% as the most influencing factors contributed to drug addict on relapse. Future research suggestions are made, in particular advocating the replication of this study to a wider population and to use more qualitative data. Also, confirmatory studies with regards to the findings would be beneficial.